Multi-wavelength mode-locked thulium-doped fiber laser based on a fiber-optic Fabry–Perot interferometer and a nonlinear optical loop mirror. (14th June 2018) - Wang, M; Huang, Y J; Yang, J W; Zhang, Y; Ruan, S C
Abstract: An all-fiberized multi-wavelength mode-locked thulium-doped fiber laser (TDFL) based on fiber-optic Fabry–Perot interferometer (FPI) and nonlinear optical loop mirror (NOLM) has been presented. The fiber-optic FPI played the roles of wavelength selective filter and output mirror, which constructs by a single mode-hollow core-single mode fiber structure (SMF-HCF-SMF). A NOLM with wavelength-dependent cavity loss was employed to alleviate the mode competition in thulium-doped fiber and enabled the multi-wavelength mode-locking. With proper manipulation of the polarization controller and the pump power, besides the single-wavelength ( 1948 nm) fundamental and high orders harmonic mode-locked operations, switchable dual-wavelength (1924.67/1949.16 nm and 1949.64/1972.68 nm) and stable three-wavelength (1924.80/1951.42/1972.14 nm) mode-locked operations are obtained. The multi-wavelength mode-locked TDFL exhibits a good stability with maximum peak power fluctuations of less than 0.5 dB in 2 h.